Targeting Neutrophils for Promoting the Resolution of Inflammation - Filep, János G. (Frontiers in Immunology, 2022)
Acute inflammation is a localized and self-limited innate host-defense mechanism against invading pathogens and tissue injury. Neutrophils, the most abundant immune cells in humans, play pivotal roles in host defense by eradicating invading pathogens and debris. Ideally, elimination of the offending insult prompts repair and return to homeostasis. However, the neutrophils` powerful weaponry to combat microbes can also cause tissue damage and neutrophil-driven inflammation is a unifying mechanism for many diseases. For timely resolution of inflammation, in addition to stopping neutrophil recruitment, emigrated neutrophils need to be disarmed and removed from the affected site. Accumulating evidence documents the phenotypic and functional versatility of neutrophils far beyond their antimicrobial functions. Hence, understanding the receptors that integrate opposing cues and checkpoints that determine the fate of neutrophils in inflamed tissues provides insight into the mechanisms that distinguish protective and dysregulated, excessive inflammation and govern resolution. This review aims to provide a brief overview and update with key points from recent advances on neutrophil heterogeneity, functional versatility and signaling, and discusses challenges and emerging therapeutic approaches that target neutrophils to enhance the resolution of inflammation.